Bangladesh : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This report describes economic developments in Bangladesh during the 1990s. Macroeconomic performance deteriorated beginning in 1994/95. Although production was underpinned by revived private sector activity, particularly in manufacturing, construction and trade, the impact on GDP growth was mitigated by a prolonged drought, which severely depressed agricultural production. The shortfall in food supplies resulted in sharp increases in imports of food grains and in the domestic prices of food. As domestic demand remained strong, inflation picked up and the external current account deficit more than doubled in 1994/95.